Development of a data acquisition system to optimizing the agricultural tractor performance - Serrano, João (2012)
Soil working operations in conventional farming systems involving the use of tractors are some of the operations which incur the highest energy costs. Sustainability of such systems requires strictly-controlled management of resources which can lead to a significant reduction in crop-production costs, derived from savings in fuel consumption. A novel data acquisition system has been successfully integrated on-board the Massey Ferguson 3000 series agricultural tractors for measuring tractor-implement performance. A commercial load cell was incorporated into the existing system for the needed tractor-implement performance measurements. This system is capable of measuring, displaying and recording, in real-time, the tractor’s theoretical travel speed, the actual travel speed, the engine speed, the fuel consumption rate, and the drawbar pull. Static calibration tests on various associated sensors for the required measurements show excellent linearity with correlation coefficients that are close to 1. The developed system has been extensively and successfully field demonstrated for tractor-implement performance with offset disc harrows on dry, undisturbed loamy soils. Under these conditions, a ratio of tractor power to implement width is suggested. The data also show the existence of a linear relationship between fuel consumption per hectare and specific draught, for the 4 to 9 kN m-1 range, which suggests the possibility of extending the ASABE model of draught prediction to forecast fuel consumption. The configuration of the tractor-harrow combination, based on the measurement of the draught required under operational conditions, provides the manufacturers with a reliable indication of the recommended power required for each harrow model. With this type of information farmers can make decisions regarding selection of a suitable tractor-implement combination for their farms. As a consequence, there is improved tractor-harrow productivity and field efficiency.